Remote control powerboat II (boat construction and engine installation) - Hashim, Mohammad (Universiti Malaysia Sarawak (UNIMAS), 2004)
Remote control system device is one of the branch electronic fields, which are widely used in our daily life. This project is a remote control powerboat with engine 33 c.c.. In this project, it explain in detail about the construction of the remote control powerboat which combines electronic and mechanical skills.